2020
DOI: 10.1038/s41366-020-00704-2
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of low-calorie sweeteners on energy intake and body weight: a systematic review and meta-analyses of sustained intervention studies

Abstract: The effects of low-calorie sweeteners on energy intake and body weight: a systematic review and meta-analyses of sustained intervention studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 90 publications
(577 reference statements)
8
55
1
2
Order By: Relevance
“…Similar results were obtained by Rogers et al [ 83 ] in a systematic review with meta-analysis. Studies comparing the efficacy of sucrose and NNS found a greater reduction in body weight and BMI, and a more significant reduction in energy intake in the group using NNS.…”
Section: Sweeteners: Implications For Energy Intake and Body Weight R...supporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were obtained by Rogers et al [ 83 ] in a systematic review with meta-analysis. Studies comparing the efficacy of sucrose and NNS found a greater reduction in body weight and BMI, and a more significant reduction in energy intake in the group using NNS.…”
Section: Sweeteners: Implications For Energy Intake and Body Weight R...supporting
confidence: 91%
“…Studies comparing the efficacy of sucrose and NNS found a greater reduction in body weight and BMI, and a more significant reduction in energy intake in the group using NNS. Additionally, weight loss was found to correlate positively with the percentage of sucrose replaced by sweeteners [ 83 ].…”
Section: Sweeteners: Implications For Energy Intake and Body Weight R...mentioning
confidence: 99%
“…Specifically, the findings that (1) reduced body weight, BMI, and body fat were associated with the use LNCSBs as a substitute for SSBs with caloric displacement and (2) neutral outcomes were associated with the use of LNCSBs as a substitute for water without caloric displacement are consistent with the results of other systematic reviews and meta-analyses of RCTs. [48][49][50][51] Figure Decreases in body weight, 48,49 body weight and BMI, 50 and a composite of body weight or BMI 51 were observed with the substitution of LNCSs for a caloric comparator (sugars in foods or beverages) predominantly in participants with overweight or obesity. Miller and Perez 50 further showed reductions in fat mass and waist circumference.…”
Section: Findings In the Context Of Existing Studiesmentioning
confidence: 99%
“…LNCS provide the pleasure of sweet taste without the energy content of sugar [24], and the safety and use of many LNCS in humans have been approved [24][25][26]. Consistent with work demonstrating benefits for weight management [27,28], LNCS use continues to be predominantly associated with concerns over bodyweight [14,16,[29][30][31]. Consumers, however, also cite concerns over safety [32], poor taste [16], their artificial or chemical nature [14,16,31] and possible health implications [14,16], and similar concerns have been expressed by dietitians [23].…”
Section: Introductionmentioning
confidence: 79%